The battle of narratives between the powers: party hyperfragmentation, judicialization of politics and supremocracy in the Brazilian political-institutional system - Santa Brígida, Yasmim Salgado; Verbicaro, Loiane Prado (Revista de Investigações Constitucionais, 2020)
It is analyzed to what extend the battle of narratives between the powers demonstrates the weakening of democracy in the Brazilian political system, from the challenge raised by the phenomena of party hyperfragmentation, the judicialization of politics and supremocracy. The battle between the powers in the Brazilian institutional context is presented through the analysis of the political and judicial changes resulting from the STF's stance in the Impeachment process of former President Dilma Rousseff, Mensalão and Lava Jato´s Operation. Modified institutes at this juncture are related to the coalitions of party hyperfragmentation, the judicialization of politics, and the supremocracy. The research is qualitative bibliographic with analysis of studies on democratic theories and constitutional law, by Oscar Vilhena Vieira and the sociological research of Sérgio Abranches. It follows that debate is needed for the consolidation of a substantial democratic system based on respect for the principles of human dignity in order to avoid constitutional "malaise" and authoritarianism.